Consumer Buying Behavior towards Precious Metals and Jewelries in Nepalese Market - Khadkathoki, Arpan (Nepalese Journal of Management, 2024)
This study examines the influence of consumer buying behavior towards precious metals and jewelries in Nepalese market. Consumer buying behavior is the selected dependent variable. The selected independent variables are price, purity, design, brand image, advertisement, and product quality. The primary source of data is used to assess the opinions of the respondents regarding the consumer buying behavior towards precious metals and jewelries. The study is based on primary data with 122 respondents. To achieve the purpose of the study structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and influence of selected independent variables on consumer buying behavior towards precious metals and jewelries in Nepalese market. The study showed that price has a positive impact on consumer buying behavior. It implies that fairness in price of precious metal simulates the buying behavior of consumers towards precious metal and jewelry. The study also revealed that purity has a positive impact on consumer buying behavior. It implies that increase in purity of jewelry simulates the buying behavior of consumers. Moreover, design has a positive impact on consumer buying behavior. It implies that better the designs of jewelry, more it stimulates the consumer buying behavior. Furthermore, brand image has a positive impact on consumer buying behavior indicating that good brand image stimulates the consumer buying behavior. The study also showed that advertisement has a positive impact on consumer buying behavior. It implies that increase in advertisement of jewelry stimulates the buying behavior of consumer. Similarly, the study also showed that product quality has a positive impact on consumer buying behavior. It indicates that better quality of jewelry stimulates the buying behavior of consumers.